Doing More With Less : The New Way to Wealth - Piasecki, Bruce, 1955- (Hoboken John Wiley, 2012)
After the last set of business scandals and financial busts, many powerful interests and many influential people are asking questions about doing more with less, from governments to multinational corporations; they are seeking this realignment in hopes of regaining their balance. Doing More with Less is an actionable call to arms, with global insights--that are of immediate application to professionals in any industry--into new ways to better align money, people, and rules. Author, Bruce Piaceski, convincingly lays out the case for a return to frugality, providing relevant examples from his thirty years of experience as a management consultant and change agent. Piaceski deftly explains how this approach to competition is relevant, and provides readers with the framework to look at what's next without tottering toward failure.
Include Index
Keywords: Wealth -- Thriftiness -- Competition